Selective activity of butyrylcholinesterase in serum by a chemiluminescent assay - Yavo, B.; Brunetti, Iguatemy Lourenço [UNESP]; Fonseca, Luiz Marcos da [UNESP]; Catalani, L. H.; Campa, A. (Wiley-Blackwell, 2001)
In a previous study, we showed that purified commercial esterase activity can be detected in a chemiluminescent assay based on the hydrolysis of 2-methyl-1-propenylbenzoate (MPB) to 2-methyl-1-propenol, which is subsequently oxidized by the horseradish peroxidase (HRP)-H2O2 system. The purpose of this study was to verify the applicability of this assay to human serum. The existence of an esterase activity capable of hydrolysing MPB is indicated by the fact that the MPB-scruin-HRP-H2O2 System consumes oxygen and emits light. Both signals were abolished by prior serum heat inactivation and were preserved when serum was stored at less than or equal to4 degreesC. Addition of aliesterase inhibitors, such as fluoride ion and trichlorfon or the cholinesterase inhibitor eserine, totally prevents light emission. The butyrylcholinesterase-specific substrate benzoylcholine causes a delay in both O-2 uptake and light emission, while the specific acetylcholinesterase substrate, acetyl-beta -methylcholine, had practically no effect. Purified butyrylcholinesterase, but not acetylcholinesterase, triggered light emission. The finding that butyryleholinesterase is responsible for the hydrolysis of MPB in serum should serve as the basis for the development of a specific chemiluminescent assay for this enzyme. Copyright (C) 2001 John Wiley & Sons, Ltd.
Keywords: esterase; butyrylcholinesterase; pseudocholinesterase; horseradish peroxidase; chemiluminescence